Management of Arabic Language Learning Based on Self-Regulated Learning and Its Application at The Modern Islamic Boarding School - Musgamy, Awaliah; Rusydi, Muhammad (International Journal of Social Learning (IJSL), 2024)
The background of the research shows that the strategy carried out by the modern Islamic boarding school in the implementation of Arabic language learning management based on self-regulated learning is a distinctive scientific phenomenon. This study examines the application of self-regulated learning-based Arabic language learning management. As a field research through qualitative research with a phenomenological paradigm, the research data was obtained through interviews, observations, documentation, and reference searches to be further processed and analyzed through reduction, exposure, and conclusion of data. The study results show that the components of self-regulated learning, which in this case consist of motivation regulation, planning, effort regulation, attention focusing, task strategies, using additional resources, and self-instruction, can be identified which are applied to sit students as creative learning subjects. The conclusion shows that applying various self-regulated learning components contributes to shaping students' creativity in participating in Arabic language learning.